Penerapan Model Pembelajaran Osborn Untuk Meningkatkan Hasil Belajar Siswa Dalam Materi Himpunan Pada Siswa Kelas VII MTS Negeri 2 Bolaang Mongondow Utara - Iman, Rivo Syahputra; Badu, Syamsu Qamar; Isa, Dewi Rahmawaty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Inappropriate teaching models can hinder the effectiveness of learning and negatively impact students' learning outcomes. Conversely, the implementation of suitable teaching models can provide a better learning experience and support the achievement of learning objectives. The Osborn teaching model is one appropriate approach to enhancing students' learning outcomes, especially in the topic of sets. This model emphasizes active student participation in generating ideas and problem-solving through brainstorming techniques. By granting students the freedom to express themselves and collaborate within groups, the Osborn model helps increase student engagement in learning and enrich their understanding of the subject matter. Therefore, through the implementation of the Osborn teaching model, it is expected that students' learning outcomes in the topic of sets will significantly improve. Research results confirm that the application of the Osborn model has a significant positive impact on students' learning outcomes in the subject of sets. There was a consistent improvement from cycle I to cycle II, where average learning outcomes increased significantly. This improvement was observed in the affective, psychomotor, and cognitive domains, with percentages increasing from the previous cycle. Evaluations conducted in each cycle demonstrate the effectiveness of the Osborn model in deepening students' understanding of set concepts. The final results indicate that the average learning outcomes of students have met the minimum success indicator of 80%, illustrating that the implementation of the Osborn model has successfully enhanced overall student learning achievements in understanding the set material.